Prevention of dental caries in Indigenous children from World Health Organization–listed high-income countries: A systematic review. (April 2018) - Smith, Leanne; Blinkhorn, Fiona A; Blinkhorn, Anthony S; Hawke, Fiona
Objective: To systematically review evidence for interventions to prevent early childhood caries (ECC) in Indigenous children in high-income countries. Search strategy: In November 2016, we searched Medline (from 1946), Embase (from 1980), the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed (from 1996) and the Cumulative Index to Nursing and Allied Health Literature (CINAHL) (from 1982) for randomised and quasi-randomised controlled trials including children aged 0–5 years. Outcomes included the decayed, missing and filled teeth (dmft) index or similar index; the number of children with reported pain or emergency dental visits because of pain; the number of children referred for dental care; plaque scores; the amount of oral debris present; change in parent/carer attitude or knowledge towards baby teeth; reported regular dental visits and adverse outcomes. Two authors independently screened for inclusion and assessed the risk of bias. Main results: Four trials reported in five papers with 2, 311 participants were included. Interventions were fluoride varnish with counselling/health promotion, chlorhexidine varnish, and motivational interviewing techniques plus oral hygiene materials and a dental examination. Two trials showed fluoride varnish applied biannually over a 2-year period reduced caries prevalence (mean difference [MD]: –3.00; 95% confidence interval [CI]: –4.94 to −1.06; MD: –2.47; 95% CI: –2.57 to −2.37). Motivational interviewing with oral hygiene materials and a dental examination can reduce the number of carious lesions in children aged 30 months (d2–4 efs > 0 MD: –5.10; 95% CI: –8.74 to −1.46; d3–4 efs > 0; MD: –4.40; 95% CI: –7.55 to −1.25). Conclusion: Fluoride varnish applied biannually over 2 years is effective at reducing ECC in Indigenous children. Motivational interviewing has some benefit in caries prevention. Further research is required to test other preventive programmes.